2018
DOI: 10.1002/pon.4705
|View full text |Cite
|
Sign up to set email alerts
|

A screening algorithm for early detection of major depressive disorder in head and neck cancer patients post‐treatment: Longitudinal study

Abstract: Our results outline the predominant role of anxiety upon diagnosis as a precursor to post-treatment Major Depressive Disorder, suggesting the need for identification and prophylactic treatment of anxiety upon diagnosis in head and neck cancer patients. Further investigation into pathways by which pre-treatment anxiety predisposes to post-treatment Major Depressive Disorder in this population is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 45 publications
(61 reference statements)
0
28
0
Order By: Relevance
“…In total 33 of these articles fulfilled the eligibility criteria. In addition, two studies were included after screening the reference lists, resulting in 35 articles . These 35 articles provided results on 27 separate studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total 33 of these articles fulfilled the eligibility criteria. In addition, two studies were included after screening the reference lists, resulting in 35 articles . These 35 articles provided results on 27 separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…In Table , the characteristics of the 35 included studies are described. Twenty‐one studies reported on factors associated with depression at a single time point, 10 studies on factors associated with the course of depression and four on both . Results on factors associated with depression at a single time point and the course of depression are presented separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations